Complex Interactions Between Sex and Stress on Heroin Seeking - Carter, Jordan S.; Kearns, Angela M.; Reichel, Carmela M. (Frontiers in Neuroscience, 2021)
Rationale: Stress plays a dual role in substance use disorders as a precursor to drug intake and a relapse precipitant. With heroin use at epidemic proportions in the United States, understanding interactions between stress disorders and opioid use disorder is vital and will aid in treatment of these frequently comorbid conditions. Objectives: Here, we combine assays of stress and contingent heroin self-administration (SA) to study behavioral adaptations in response to stress and heroin associated cues in male and female rats. Methods: Rats underwent acute restraint stress paired with an odor stimulus and heroin SA for subsequent analysis of stress and heroin cue reactivity. Lofexidine was administered during heroin SA and reinstatement testing to evaluate its therapeutic potential. Rats also underwent tests on the elevated plus maze, locomotor activity in a novel environment, and object recognition memory following stress and/or heroin. Results: A history of stress and heroin resulted in disrupted behavior on multiple levels. Stress rats avoided the stress conditioned stimulus and reinstated heroin seeking in response to it, with males reinstating to a greater extent than females. Lofexidine decreased heroin intake, reinstatement, and motor activity. Previous heroin exposure increased time spent in the closed arms of an elevated plus maze, activity in a round novel field, and resulted in object recognition memory deficits. Discussion: These studies report that a history of stress and heroin results in maladaptive coping strategies and suggests a need for future studies seeking to understand circuits recruited in this pathology and eventually help develop therapeutic approaches.